2021
DOI: 10.1021/acsapm.1c00802
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic Sandwich Structure Aerogel Membrane for Emulsion Separation and Heavy Metal Ion Removal

Abstract: Water pollution has been increasingly becoming a serious environmental and health challenge in recent years. This is compounded by the often coexisting oil pollution and heavy metal pollution. It is of great practical significance to develop materials that can simultaneously deal with these two kinds of water pollution problems. In this study, a simple and green approach is proposed for preparing matrix-free citric acid modified alginate-based aerogel membrane by simple sol spraying, chemical cross-linking, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…To more precisely describe the adsorption kinetics and test its anti-interference ability, we then plotted the adsorption isotherms of TPPA-SO 3 H to Fe 3+ , Cr 3+ , and Cd 2+ ions against the initial concentrations and adsorption times (Figure e,f). , The studies of the pH value effect revealed that TPPA-SO 3 H showed the most excellent adsorption capability to all three ions under near neutral conditions (pH ≈ 6.5, Figure S16). Meanwhile, the imine bonds are easily hydrolyzed under strongly acidic and basic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To more precisely describe the adsorption kinetics and test its anti-interference ability, we then plotted the adsorption isotherms of TPPA-SO 3 H to Fe 3+ , Cr 3+ , and Cd 2+ ions against the initial concentrations and adsorption times (Figure e,f). , The studies of the pH value effect revealed that TPPA-SO 3 H showed the most excellent adsorption capability to all three ions under near neutral conditions (pH ≈ 6.5, Figure S16). Meanwhile, the imine bonds are easily hydrolyzed under strongly acidic and basic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane filtration as a simple and easy ion removal method has wide applicability in industry. , We then pressed the powders of three samples into three membranes with diameters of about 2.0 cm (Figure a–c) and tested their capabilities for removal of metal ions by membrane filtration separation methods. Before each membrane is fixed in the middle of the home-made equipment, as shown in Figure d, the water contact angle was first tested.…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of GPM Purification Material. According to a previous report, 37 the above prepared sols were uniformly sprayed onto the ice surface of calcium chloride (2%) to form solid sol. In particular, the SA sol and SA@PEI@WPU blended sol were sprayed in stages.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our previous work, a kind of graded functional purification material was designed in this study to purify complex sewage through filtration. As shown in Figure , the purification material herein reported has a secondary structure, consisting of an SA@WPU@WPU functional layer and an SA isolation layer.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported a citric acid free modified alginate based aerogel film, which possessed a hierarchical microstructure with dense upper and lower surfaces and loose middle layers as shown in Figure 23b. 220 The prepared aerogel film exhibited super hydrophilic and underwater super oil repellent properties and strong adhesion resistance and could realize the separation of highly viscous miscible oil−water emulsions even in a orrosive and high salt environment, and the separation efficiency was more than 99.5%. In the process of continuous cross-flow filtration of emulsion for 3000 min, the membrane showed strong stability, which reflected that the membrane had good long-term separation performance.…”
Section: Pressure Sensorsmentioning
confidence: 98%